PREDIKTOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN DI THE BREEZES BALI RESORT & SPA SEMINYAK - Suryanatha, A.A. Ngr. Bayu; Sudibya, I Gde Adnyana; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
This study aims to 1) analyze the influence of employee satisfaction on organizational commitment, 2) analyze the influence of employee satisfaction on organizational citizenship behavior (OCB), 3) analyze the effect of organizational commitment on organizational citizenship behavior (OCB) and 4) to analyze the role of mediation commitment the organizational influence employee satisfaction on OCB. The population in this study were all employees of The Breezes Bali Resort & Spa Seminyak. Data collected through observation, questionnaires and interviews. Data analysis technique used is PLS (Partial Least Square). Based on the results obtained in this study 1) Job satisfaction positive and significant effect on organizational commitment, 2) Job satisfaction positive and significant effect on organizational citizenship behavior (OCB), 3) Commitment organizational positive and significant effect on organizational citizenship behavior (OCB) and 4) organizational commitment mediates the influence of employee satisfaction on OCB.
Keywords: job satisfaction, organizational commitment and organizational citizenship behavior (OCB).